1980
DOI: 10.1002/ana.410080319
|View full text |Cite
|
Sign up to set email alerts
|

An autosomal dominant syndrome of hemiplegic migraine, nystagmus, and tremor

Abstract: A mother and son suffer from hemiplegic migraine with onset in childhood. Both have nystagmus which has not changed for many years, but the date of onset is uncertain. They have an asymmetrical tremor, clinically indistinguishable from essential tremor. Neuroophthalmological examination revealed inability to produce smooth pursuit, gaze-paretic nystagmus, rebound nystagmus, failure of fixation suppression of the vestibuloocular reflex both horizontally and vertically, and low gain of the optokinetic system. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 3 publications
0
31
0
Order By: Relevance
“…A study of 20 families with benign essential tremor reported that 26% of affected members also co-segregated for migraine with aura [23]. Interestingly, essential tremor has been reported in some FHM1-linked families who also have cerebellar dysfunction and in another FHM family with nystagmus and ocular motility changes suggestive of brainstem-cerebellar dysfunction.…”
Section: Comorbidity: Migraine Associated With Other Disordersmentioning
confidence: 99%
“…A study of 20 families with benign essential tremor reported that 26% of affected members also co-segregated for migraine with aura [23]. Interestingly, essential tremor has been reported in some FHM1-linked families who also have cerebellar dysfunction and in another FHM family with nystagmus and ocular motility changes suggestive of brainstem-cerebellar dysfunction.…”
Section: Comorbidity: Migraine Associated With Other Disordersmentioning
confidence: 99%
“…Most cases showed vasodilation or hyperperfusion during aura, which can differentiate this condition from ischemia (15-18). However, vasoconstriction was reported in a few cases (19, 20). Neither the severity of symptoms nor the time point of evaluation explained this discordance.…”
Section: Discussionmentioning
confidence: 99%
“…96 In children, rebound nystagmus may accompany gaze-evoked nystagmus in many inherited conditions, including paroxysmal hereditary ataxias, 97 giant axonal neuropathy, 98 and familial hemiplegic migraine. 99 Bruns Nystagmus Occasionally, a tumor of the cerebellopontine angle becomes large enough to cause a small-amplitude, high-frequency nystagmus on contralateral gaze, and large amplitude, low-frequency nystagmus on ipsilateral gaze. The former results from disruption of ipsilateral afferent vestibular input (secondary to compromise of the eight cranial nerve), which causes the eyes to drift back toward primary position from contralateral gaze; this defect results in generation of corrective saccades away from the side of the lesion.…”
Section: Caloric-induced Nystagmusmentioning
confidence: 99%